2009
DOI: 10.1007/s00423-009-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of receptor tyrosine kinases c-kit, EGF-R, and PDGF-R in colorectal adenocarcinomas

Abstract: Our study confirms that expression of the tyrosine kinases c-kit and PDGF-R are rare in colorectal carcinomas and do not correlate with tumor stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
2
6
0
Order By: Relevance
“…This suggests that expression of c-Kit in colon tumors is rare; thus, it is not a marker of choice in the colon. These findings are in accordance with Friederichs et al (38). Yet, the increased expression after several dose of chemotherapy can indicate a change in receptor expression pathway of stem cells, or an alteration in the tyrosine-kinase receptors.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that expression of c-Kit in colon tumors is rare; thus, it is not a marker of choice in the colon. These findings are in accordance with Friederichs et al (38). Yet, the increased expression after several dose of chemotherapy can indicate a change in receptor expression pathway of stem cells, or an alteration in the tyrosine-kinase receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Several immunohistochemical studies in colorectal cancer also detected a reduction in c-Kit that is associated with later stages of tumor development (29,30). However, studies on c-Kit expression in normal human colon and colon cancer tissue showed contradicting results: originally, c-Kit was detected throughout human adult and fetal tissues and in the colonic mucosa, submucosa, and intestinal smooth muscle layers (31).…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: We read with great interest the contribution by Friederichs and colleagues regarding immunohistochemical detection of the receptor tyrosine kinases c-kit, EGF-R, and PDGF-R in colorectal adenocarcinomas [1]. The authors showed EGF-R expression in only 15.3% of cases; emphasized that activity of tyrosine kinase inhibitors does not necessarily correlate with the tyrosine kinase expression of the tumors; showed that there is no correlation between EGF-R in colorectal cancer, clinical response to anti-EGF-R antibodies, and outcome; and that pretreatment selection of patients cannot be based on immunohistochemical expression of EGF-R.…”
mentioning
confidence: 99%